Rights of abandoned child (foundling): Protection of the rights to identity: registration of birth and citizenship under the Malaysian law - Mohd, Azizah (2007)
The law of protection of children rights including abandoned child (foundling) in Malaysia was reformed by virtue of the Child Act 2001 quite immediately after ratification of the United Nations Convention on the Rights of the Child (UNCRC) by Malaysian government in 1995. Besides the fact that the Child Act 2001 is enshrined with the spirit of the UNCRC, provisions on protection of the rights abandoned child identity, registration of birth and citizenship are missing and scattered in another statutory provisions. This paper seeks to discuss the law relating to protection of the rights of abandoned child to identity, registration of birth and citizenship under Civil law that applicable to both Muslims and Non Muslims children in Malaysia and the Islamic law (the Shari'ah). The paper will examine the extent to which the law could provide a just and equitable rule in protecting the rights of abandoned child in those matters. The discussion will also hoghlight the provisions under the UNCRC which emphasize on the obligation of the State Party to protect a child's identity which includes his name, nationality and family ties. Finally, the paper will provide comments and suggestions to improve the current law in Malaysia if any.